CLINICAL AND MORPHOLOGICAL CHARACTERISTICS OF DISTURBANCES OF LOCAL IMMUNE RESPONSE IN ALOPECIA AREATA ACCORDING TO THE DISEASE ACTIVITY - G. P. Tereshchenko (Сеченовский вестник)
Aim. Description of morphological characteristics of alopecia areata according to the disease activity.Methods. Skin biopsies from scalp of patients with alopecia areata were studied: expression of CD4+, CD8+, CD68+, interleukin-2 (IL-2), interferon-y (IFN-y) and tumor necrosis factor a (TNF-a) was assessed.Results. In alopecia areata local inflammatory CD4+- and CD8+-mediated cytotoxic immune response develops with participation of proinflammatory cytokins (IL-2, IFN-y, TNF-a). Corellation between clinical and morphological signs of alopecia areata activity can be seen.Conclusion. Local skin immune-mediated inflammatory response in alopecia areata can be considered as target for pathogenetic therapy.